The dialectical transformation of Javanese mantras in the aesthetic construction of modern Indonesian poetry by Sapardi Djoko Damono - Mulyono, Mulyono; Qomariyah, U'um; Utomo, Asep Purwo Yudi; Prabaningrum, Dyah; Neina, Qurrota Ayu (citeus, 2025)
Mantras are an ancient form of poetry believed to possess a powerful ability to cure diseases, protect oneself, ward off misfortune, and foster love. Beyond those practical interests, Javanese mantras also contain philosophical values regarding the relationship between humans and God, humans and humans, and humans and the universe. These mantras become especially intriguing when reimagined in the form of modern poetry, as seen in the work of Sapardi Djoko Damono. This study explores the forms of transformation that Javanese mantras undergo in the poems by focusing on the following questions: 1) What are the forms of transformation of Javanese mantras in Sapardi's poems? 2) Can the magical power of mantras be maintained with changes in form, language, value, motivation, etc.? 3) How does it affect the promotion of culture and the development of national mentality? This process of transformation is understood as a dialectical one, representing a form of dialectical hermeneutics, involving a dynamic interplay between the researcher, the text, the author, and the broader context surrounding the text. Findings show that the dialectical transformation of Javanese mantras in modern poetry enriches aesthetic and spiritual insights. Promoting a better understanding of this transformation may help address concerns about a return to irrational thinking in society.